Frequency and synchronisation features of a highly overlapped duet changes according to the context - Méndez Vázquez, Carolina (2019)
Territorial defence and maintaining contact are two hypotheses of duet functions. Nevertheless, the acoustic characteristics of duets in these contexts have been poorly quantified. This work aimed to compare the spectrotemporal characteristics and synchronisation in White-eared Ground-sparrow duets produced in aggressive context (i.e. territorial defence) and non-aggressive context (i.e. paircontact). We expected to observe differences when compare duets of the same pair in each context. For this, we recorded 35 pairs in each context: territorial defence and pair-contact. We measured duration, minimum, highest, and maximum amplitude frequency. Synchronisation was measured comparing time and frequency bandwidth variation in three sections of duets produced in both contexts. In territory defence contexts, duets showed lower minimum frequencies and were produced with lower frequency synchronisation between first and middle section bandwidth; but with higher frequency synchronisation between middle and final section bandwidth. This suggests that this ground-sparrow encode context-depend information changing the frequency characteristics of duets. For example, to decrease the minimum frequency on the duets produced in territorial defence context could be understood as a most aggressive signal to the intruder, because in several species low-frequency sounds are associated with higher probability to attack the intruders or with larger and dominant individuals.